New WC-Cu thermal barriers for fusion applications: high temperature mechanical behaviour - Tejado, Elena (2018)
ABSTRACT: The combination of tungsten carbide and copper as a thermal barrier could effectively reduce the thermal mismatch between tungsten and copper alloy, which are proposed as base armour and heat sink, respectively, in the divertor of future fusion reactors. Furthermore, since the optimum operating temperature windows for these divertor materials do not overlap, a compatible thermal barrier interlayer between them is required to guarantee a smooth thermal transition, which in addition may mitigate radiation damage. The aim of this work is to study the thermo-mechanical properties of WC-Cu cermets fabricated by hot pressing. Focus is placed on the temperature effect and composition dependence, as the volume fraction of copper varies from 25 to 50 and 75 vol%. To explore this behaviour, fracture experiments are performed within a temperature range from room temperature to 800 degrees C under vacuum. In addition, elastic modulus and thermal expansion coefficient are estimated from these tests. Results reveal a strong dependence of the performance on temperature and on the volume fraction of copper and, surprisingly, a slight percent of Cu (25 vol%) can effectively reduce the large difference in thermal expansion between tungsten and copper alloy, which is a critical point for in service applications. The thermal performance of these materials, together with their mechanical properties could indeed reduce the heat transfer from the PFM to the underlying element while supporting the high thermal stresses of the joint. Thus, the presence of these cermets could allow the reactor to operate above the ductile to brittle transition temperature of tungsten, without compromising the underlying materials.